Business espionage : risks, threats, and countermeasures - Wimmer, Bruce (Waltham, MA : Butterworth-Heinemann, 2015)
Business Espionage: Risk, Threats, and Countermeasures provides the best practices needed to protect a company's most sensitive information. It takes a proactive approach, explaining the measures and countermeasures that can be enacted to identify both threats and weaknesses. The text fully explains the threat landscape, showing not only how spies operate, but how they can be detected. Drawn from the author's 40 years of experience, this vital resource will give readers a true understanding of the threat of business spying and what businesses can do to protect themselves. It is ideal for use as a tool to educate staff on the seriousness of the threat of business espionage.
Includes index.
Online resource; title from PDF title page (ScienceDirect, viewed April 1, 2015).
Elsevier
Keywords: Business intelligence; Confidential business information; Business intelligence; Confidential business information; Electronic books